Pengaruh Manajemen Laba terhadap Kinerja Keuangan di Moderasi Tanggung Jawab Sosial Perusahaan - Ria Karina; Diana Rosmery (Jurnal Ekonomi Akuntansi dan Manajemen, 2023)
The purpose of this study was to determine the effect of earning management on financial performance and the effect of corporate social responsibility (CSR) as the moderating effect. Population in this study comes from secondary data of non-financial company listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. Final samples of this study were 1371 companies sorted based on purposive sampling technique. The result of this study indicated that earning management have significant effect on financial performance and corporate social responsibility and significantly moderates the effect of earnings management on financial performance measured by ROA and Tobin's Q, but does not moderate the effect of earnings management on financial performance as measured by ROE. Keywords: Financial performance, Return on Equity, Return on Asset, Earnings Management, Corporate Social Responsibility